REDIOSPECTROSCOPIC FEATURES OF LOW-DIMENSIONAL SYSTEMS - Ali Noor, Hussien (Al-Qadisiyah Journal of Pure Science, 2017)
This work presents the experimental conditions leading to changing of the line form in elec-tron paramagnetic resonance (EPR) spectra when the extreme properties (line width and intensity) of the object diagnosed are combined with different spectrum recording modes. A change in the line form on recording in the standard mode with the automatic control of a microwave oscillator over the measuring cavity is characteristic for samples with high concentrations of the paramagnetic centers. As the EPR signal intensity is growing, first the line width and symmetry is varying monotonically with a transition to the â€dipsâ€Â«the disruptionÂ», and then Ð° hysteresis is revealed for the spectral lines recorded on increasing and decreasing of a magnetic field.